Jurisdictional control of public policies in brazil: some parameters for the judiciary's activities in the concretization of social fundamental rights - de Andrade, Luiz Gustavo (Universidad Nacional del Litoral, 2018)
The present work aims to study the exercise of each of the state powers, verifying the prevalence of one over the other, or because this exercise is exaggerated, in a way that one of the Powers surpasses others, or because others do not give the exercise the intensity that would be normal. In a country of Late Modernity, such as Brazil, the inefficiency of basic public policies undoubtedly leads to a judicialization of issues that affect the implementation of social rights. It was verified that this judicial activism, shaped and organized in the wake of post-positivism, has encountered frontal resistance in the political class, which protests against the supposed attacks of the Judiciary, to what it calls the sovereignty of the vote, to make reference to the legitimacy of the acts of the administrators, since they are based on a mandate of political representation democratically conquered. The methodological procedure adopted consisted in the study of cases of jurisprudence, in particular the Brazilian Supreme Court, which, little by little, has established positions that represent important parameters to verify the limit of the jurisdictional action. It is concluded that the unconstitutional state of affairs, the existential minimum and non-intervention in purely political issues are part of such parameters.